2001
DOI: 10.1038/sj.leu.2402175
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of human thymic stromal lymphopoietin (TSLP) and signaling mechanisms leading to proliferation

Abstract: Thymic stromal lymphopoietin (TSLP) is a novel cytokine that was found to promote the development of murine B cells in vitro.Here we describe the cloning and characterization of the human homologue of murine TSLP. This protein, which is expressed in a number of tissues including heart, liver and prostate, prevented apoptosis and stimulated growth of the human acute myeloid leukemia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
143
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 24 publications
1
143
1
1
Order By: Relevance
“…Although TSLP has been associated with inflammatory responses, the factors that regulate its expression remain unclear. Studies showed that epithelial cells, primarily in the lung, skin, and gut, are the primary sources of TSLP in humans (7). Because AECs in human asthmatics were found to have increased TSLP mRNA (11), and TSLP levels in the lungs of mice with antigen-induced airway inflammation displayed elevated TSLP levels (12), we chose to study the regulation of TSLP gene expression in AECs.…”
Section: Il-1␤ and Tnf-␣ Induce Human Tslp Expression From Normal Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TSLP has been associated with inflammatory responses, the factors that regulate its expression remain unclear. Studies showed that epithelial cells, primarily in the lung, skin, and gut, are the primary sources of TSLP in humans (7). Because AECs in human asthmatics were found to have increased TSLP mRNA (11), and TSLP levels in the lungs of mice with antigen-induced airway inflammation displayed elevated TSLP levels (12), we chose to study the regulation of TSLP gene expression in AECs.…”
Section: Il-1␤ and Tnf-␣ Induce Human Tslp Expression From Normal Humanmentioning
confidence: 99%
“…The TSLP receptor complex is a heterodimer that consists of a low-affinity ligand binding chain, the TSLP receptor (TSLPR), and the IL-7 receptor ␣ chain (IL-7R␣) (5,6). TSLP and TSLPR have also been identified and characterized in humans, and the human TSLP receptor complex has been shown to also be a heterodimer that is composed of the TSLPR and IL-7R␣ chains (7,8). Although the degree of sequence homology between human and mouse TSLP and between human and mouse TSLPR is quite low (43% and 39%, respectively), the expression profiles are similar in the two species, with B cells and CD11c ϩ dendritic cells being the primary cell populations expressing the TSLPR (ref.…”
mentioning
confidence: 99%
“…Stat5 was the first molecule that was shown to be phosphorylated by TSLP stimulation in both human and murine systems (2,63,95). Brown et al showed that TSLP could induce the phosphorylation of ribosomal protein S6 and 4E-BP1 in leukemic cells (33).…”
Section: Btk Protein Tyrosine Kinasementioning
confidence: 99%
“…[10][11][12][13] The low homologies of murine versus human TSLP and CRLF2 (approx. 40%) 14,15 suggest the need for novel models to study the in vivo role of TSLP in normal and malignant human B lymphopoiesis.…”
mentioning
confidence: 99%